All Days 2010
DOI: 10.2118/136574-ms
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic Surfactant Diversion: An Effective Way to Acidize Low-Temperature Wells

Abstract: A gel-based, crosslink-diverter system has been the fluid of choice for a wide range of temperature applications for carbonate acidizing treatments in Qatar. Recent field experiences with acidizing low-temperature wells (100 to 140°F) indicated the need for a chemical diverter system that develops viscosity rapidly enough to divert acid in a continuous pumping stream.A viscoelastic surfactant-(VES) based acid-diverter system was selected for a trial treatment because of its attributed phenomena of viscosity ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 9 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…Further increasing the temperature cause the breakdown of network structure (Wei et al, 2016). Viscoelastic surfactants reflect better diversion at low temperature (Toseef et al, 2010). The mechanism of degradation of rod-like micelles at various temperatures is shown in Figure S2.…”
Section: Introductionmentioning
confidence: 99%
“…Further increasing the temperature cause the breakdown of network structure (Wei et al, 2016). Viscoelastic surfactants reflect better diversion at low temperature (Toseef et al, 2010). The mechanism of degradation of rod-like micelles at various temperatures is shown in Figure S2.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 10 years, many studies on the properties of acid systems employing viscoelastic surfactants have been published. Laboratory studies of SDVA confirmed that using viscoelastic acid systems as acid diverters in the field is very efficient.…”
Section: Introductionmentioning
confidence: 99%
“…Other work presents the results of laboratory studies and field tests of VES applied to low-temperature wells (25 to 65 °C). The VES systems showed high acid diversion efficiency in low-temperature wells.…”
Section: Introductionmentioning
confidence: 99%